Welcome to research revolution in national sports science? - Shestakov, M. P.; Fomichenko, T. G. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to analyze the present situation and developmental prospects of the national sports training theory and practice. Methods and structure of the study. For the last three decades, the ongoing modeling projects have been imple- mented in different timeframes and domains, for example: 1) Small molecules: organic and inorganic compounds modeled using molecular mechanics codes to understand their repertoire and degrees of freedom [12]; 2) Biological macromolecules: RNA, DNA and protein molecules may now be modeled using molecular dynamics technologies - e.g. ribosome and RNA polymerase models available in high resolution; 3) Cellular models: molecular-genetic systemic mechanisms of bodily adaptation under extreme stressors; 4) Biomechanical models including the cardiovascular system model, respiratory system model, skeletal geometry model, neuromuscular control model for locomotion, etc.. 5) Central nervous system is the key system in the bodily systems hierarchy, and that is why subject to new models are the motor sills control and learning systems, with every skill controlled by specific neuromodulatory brain mechanisms. Computational learning models play the key role for the adaptive behavior understanding and management goals. On the whole, subject to the above modeling projects are the biological systems behind the sports-specific motor skills mastering and excelling processes; and every relevant bodily system may now be described by specific formalisms. Conclusion. Further progress of the modern computational technologies applicable in the sports science may be described by a few progress vectors. Of special importance are the efforts to create adequate data mining toolkits to analyze bodily states in the context of the newly discovered biological regularities. In the near future we expect a few breakthroughs in the hardware upgrade domain with implantable special-purpose microprocessors and new technologies to grow special artificial receptors using modern bionanomaterials inside bodily organs.